Competency-Based Medical Education (CBME)- An Incremental Boon For Undergraduate Medical Students of India - Khan, Alinawaz; Kolagi, Sanjeev I; Herur, Anita (International Journal of Medical Students, 2024)
BACKGROUND: Competency based education has been defined as a result-based program to design, implement, assess and evaluate medical education using an organizing framework of competencies. According to the vision document put forth by MCI, thi undergraduate medical education program was designed with a goal to create an Indian Medical Graduate (IMG) possessing requisite knowledge, skills, attitudes, values, and responsiveness, so that he or she may function appropriately and effectively as a "physician of first contact" of the community while being globally relevant too. Albeit the CBME curriculum has been introduced in country since 5years, but such evaluation of the curriculum has not been carried out so extensively so far. Hence, this study fulfills the need of the hour and may suggest to rectify the education system accordingly in the nation as well as being a role model for other nations. METHODS: Ethical approval was obtained from the Institutional Ethics Committee (IEC). The study population included 214 CBME exposed and 214 CBME non-exposed undergraduates of the same college. A retrospective preformed Google Form based questionnaire with digitally signed informed written consent was used to measure knowledge and attitudes of CBME exposed undergraduate graduates and CBME non-exposed undergraduate students about the peculiar concept of CBME viz. Foundation Course, Early Clinical Exposure (ECE), Attitude, Ethics and Communication (AETCOM), Objective Structured Practical Examination (OSPE). Statistical analysis was done using SPSS 19 software and appropriate statistical tests were applied. The questionnaire comprised of 4 sections: 1- Knowledge about Foundation Course components such as: Basic Life Support training, Field/Health care center visit, Time management, Stress management, Language skills, Professionalism, Biomedical waste management, IT skills, 2- Attitude, Ethics and Communication ( AETCOM), 3- Early Clinical Exposure (ECE) practice objectives: Basic science correlation, Basic clinical skills due to clinical witnessing clinical scenario, Basic clinical skills, Problem solving skills, Better retention of topics, 4- Knowledge and practice aboutObjective Structured Practical Examination (OSPE). RESULTS: At the end of the study, it was found that among CBME-exposed 76% had clear idea and 7% had No idea, whereas among CBME non-exposed 94% had No idea and 1% had clear idea about foundation course components. Regarding AETCOM, 81% Strongly agreed and 1% Strongly disagreed/disagreed among CBME-exposed; while 91% Strongly disagreed and 1% were neutral among CBME non-exposed. Among CBME-exposed, 70% practiced ECE whereas 95% CBME non-exposed never came across ECE. Among CBME-exposed, 88% were sure and 2% had no idea, while among CBME non-exposed 95% had No idea and 1% were not sure about OSCE and its components. CONCLUSION: As per the study, there is substantial difference among CBME-exposed and CBME non-exposed undergraduates, regarding knowledge, attitude and practice of key components of newly introduced Competency Based Medical Education (CBME). The increase in knowledge, communication and attitudes scores suggests CBME as an incremental boon to MBBS students. Shortcomings in the CBME curriculum may be used as a basis to bring modifications and build one of the best medical education systems, in order to bring out the most competent doctors in future.